La pluralidad de trayectorias reproductivas y las transacciones institucionales - Lerner, Susana; Quesnel, André; Yanes, Mariana (El Colegio de México A.C., 1994)
This article presents results from research carried out between 1989 and 1991 in a rural region in the state of Morelos, beginning from an analysis centered in the interactions between health agents and women. The authors take into account the main elements of the socialization trajectories of women, for instance, family background, education, etc. The authors hypothesize that the impact of health and family planning programs, and the subsequent medicalization of procreation have turned the process of mother-infant health care into a determinant arena for women's decisión-making processes on prenatal care and childbirth health services and birth control. Using both quantitative and qualitative methodologies, several reproductive trajectories were identified and analyzed, allowing an assessment, on the one hand, of the intensity of women's interactions with health institutions, their community, and their partner and, on the other hand, a characterization of the social trajectories of women as a fundamental factor in their integration with the biomedical system.